TINJUAN YURIDIS TERHADAP JUAL BELI YOUTUBE PREMIUM OLEH ONLINE SHOP DI MEDIA SOSIAL (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Youtube has a new service called YouTube Premium. YouTube Premium is officially available in Indonesia since November 6, 2019. A YouTube Premium subscription allows users to watch videos on YouTube without advertising on its website and mobile applications, including the YouTube Music app, and the YouTube Kids App, YouTube Music Premium and the Google Play Music service. Through this application, users can also save videos to their devices for offline viewing. Article 1320 of the Civil Code stipulates that the agreement must meet the validity requirements of the agreement and in Article 32 of Law Number 11 of 2008 concerning Electronic Information and Transactions, the methods relating to prohibited acts in connection with electronic information or electronic documents are regulated. So in the implementation of buying and selling YouTube premium by selling accounts, in fact it has been without rights or against the law in any way moving or transferring electronic information or electronic documents to other people's electronic systems that are not entitled.This type of research can be classified as normative juridical research, because this research is conducted by examining secondary data and approaches to the law. This normative research examines legal principles. Sources of data used are primary data, secondary data, tertiary data, data collection techniques in this research are normative juridical, data used is literature study.The results of the research conducted by the author are cases of buying and selling YouTube premium by online shops in social media is an illegal act. The act of buying and selling YouTube premium is an act of default because it violates the terms of YouTube paid service, as for the legal consequences of this sale and purchase is default, and dispute resolution can be carried out in court. The author's suggestion for this case is that there is a need for special arrangements regarding the sale and purchase of this premium account, premium YouTube users are also advised to read carefully the terms of this premium Youtube paid service. Youtube can also work with providers in Indonesia to provide payment methods via credit, making it easier for people to buy this premium Youtube directly to Youtube. There needs to be special arrangements related to this premium Youtube buying and selling case as well as buying and selling premium accounts for other applications. There is also a need for reprimands and sanctions that are given by Youtube to online shop people who sell Youtube premium as well as regular checks of the addresses of these premium Youtube account users.Keywords: Juridical Review, Buying and Selling, Youtube Premium.